2020
DOI: 10.1101/2020.06.01.20119040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with adherence to self-isolation and lockdown measures in the UK; a cross-sectional survey

Abstract: Objectives: To investigate factors associated with adherence to self-isolation and lockdown measures due to COVID-19 in the UK. Design: Online cross-sectional survey. Setting: Data were collected between 6th and 7th May 2020. Participants: 2240 participants living in the UK aged 18 years or over. Participants were recruited from YouGov's online research panel. Main outcome measures: Having gone out in the last 24 hours in those who reported symptoms of COVID-19 in their household. Having gone out shopping… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 22 publications
6
88
1
1
Order By: Relevance
“…Not being vulnerable was associated with a lower intention to socially distance, lower age, not being retired, long-term sick or disabled, and not living with a person of vulnerable health status. Our ndings on vulnerability is consistent with a crosssectional UK study (44), which found that being clinically vulnerable was associated with fewer outings. Lower control over others' distancing was associated with living in a rented room in a house of multiple occupancy and with higher perceived susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…Not being vulnerable was associated with a lower intention to socially distance, lower age, not being retired, long-term sick or disabled, and not living with a person of vulnerable health status. Our ndings on vulnerability is consistent with a crosssectional UK study (44), which found that being clinically vulnerable was associated with fewer outings. Lower control over others' distancing was associated with living in a rented room in a house of multiple occupancy and with higher perceived susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is important to note that this figure may still be optimistic, with one study reporting 62•2% of Japanese citizens surveyed went to work within seven days of onset of symptoms [39] and another that 75•1% of individuals living in a UK households with COVID-19 symptoms admit to leaving the house in the last 24 hours [40].…”
Section: Contact Tracingmentioning
confidence: 99%
“…A cross-sectional survey of a representative sample of UK adults.A cross-sectional survey of the UK adult population (18 years or older) was commissioned by the market research organisation YouGov. Full details of the method are available elsewhere 1.…”
mentioning
confidence: 99%